2022
DOI: 10.1097/ju.0000000000002270
|View full text |Cite
|
Sign up to set email alerts
|

Postchemotherapy Residual Tumor Resection in Patients with Elevated Tumor Markers

Abstract: Purpose:The oncologic benefit of postchemotherapy (PC) residual tumor resection (RTR) in patients with germ cell tumors and elevated serum tumor markers (STMs) remains unclear. This analysis was performed to better define patients who benefit from surgery in this setting.Materials and Methods:Of 575 PC-RTR procedures (July 2008–July 2019) 153 were performed in patients with elevated STMs (human chorionic gonadotropin [HCG] >2.0 mIU/ml, alpha-fetoprotein [AFP] >7.0 µg/l), including 55 after first line and 98 af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Patients with persistent elevations of AFP or BHCG after chemotherapy are at high risk of relapse after resection of residual disease. 17,21,55 A German study reported the outcomes of 153 patients who underwent PC-RPLND in the setting of elevated AFP and/or BHCG, including 55 who had received first-line chemotherapy and 98 who had received salvage chemotherapy. 55 Of the first-line chemotherapy patients, 50% relapsed, including 78% of those with an AFP > 30 ng/mL.…”
Section: Challenges In Diagnosis and Management And Review Of The Rel...mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with persistent elevations of AFP or BHCG after chemotherapy are at high risk of relapse after resection of residual disease. 17,21,55 A German study reported the outcomes of 153 patients who underwent PC-RPLND in the setting of elevated AFP and/or BHCG, including 55 who had received first-line chemotherapy and 98 who had received salvage chemotherapy. 55 Of the first-line chemotherapy patients, 50% relapsed, including 78% of those with an AFP > 30 ng/mL.…”
Section: Challenges In Diagnosis and Management And Review Of The Rel...mentioning
confidence: 99%
“…17,21,55 A German study reported the outcomes of 153 patients who underwent PC-RPLND in the setting of elevated AFP and/or BHCG, including 55 who had received first-line chemotherapy and 98 who had received salvage chemotherapy. 55 Of the first-line chemotherapy patients, 50% relapsed, including 78% of those with an AFP > 30 ng/mL. The OS for the first-line group was 65%, and it was 22% for those with an AFP > 30 ng/mL and 0% for those with a BHCG > 20 μg/L.…”
Section: Challenges In Diagnosis and Management And Review Of The Rel...mentioning
confidence: 99%
See 1 more Smart Citation